2012
DOI: 10.1002/app.38719
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rheological behavior and mechanical properties of PVC/CPE/MAP–POSS nanocomposites

Abstract: Poly(vinyl chloride)/chlorinated polyethylene (PVC/CPE)/methylacryloylpropyl-containing polyhedral oligomeric silsesquioxane (MAP-POSS) nanocomposites are prepared. The plastic behavior and dynamic rheological behavior of PVC/CPE/ MAP-POSS are investigated. The influences of composition on dynamic storage modulus G 0 , loss modulus G 00 , and complex viscosity g* of PVC/CPE/MAP-POSS melts are discussed. The dynamic mechanical properties, mechanical properties, and morphology are determined. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In many cases, it has been found that the use of polyhedral oligomeric silsesquioxanes (POSS) as nanofillers, irrespective of the functional groups (POSS) [14,15,[91][92][93][94][95][96] attached to the POSS cage, leads to the plasticizing effect of PVC, i.e., to a lowering of Tg. The influence of 10, 15, and 20 wt.% methacryl polyhedral oligomeric silsesquioxanes (POSS) on the Tg of PVC was described by Soong et al [91], who observed a monotonous decrease in the α-transition temperature and related changes in mechanical properties (lowering of storage modulus) as a clear indication of the plasticizing role of POSS on the PVC matrix.…”
Section: The Influence Of Oligomeric Silsesquioxanes On the Glass Tra...mentioning
confidence: 99%
“…In many cases, it has been found that the use of polyhedral oligomeric silsesquioxanes (POSS) as nanofillers, irrespective of the functional groups (POSS) [14,15,[91][92][93][94][95][96] attached to the POSS cage, leads to the plasticizing effect of PVC, i.e., to a lowering of Tg. The influence of 10, 15, and 20 wt.% methacryl polyhedral oligomeric silsesquioxanes (POSS) on the Tg of PVC was described by Soong et al [91], who observed a monotonous decrease in the α-transition temperature and related changes in mechanical properties (lowering of storage modulus) as a clear indication of the plasticizing role of POSS on the PVC matrix.…”
Section: The Influence Of Oligomeric Silsesquioxanes On the Glass Tra...mentioning
confidence: 99%
“…For the purpose of combining plasticization with thermostability in one chemical compound, blending of PVC with POSS would provide a prospective way to achieve the desired properties of two materials. A variety of POSS nanostructured chemicals have been prepared which contain one or more different organofunctional derivatives, and have been introduced into PVC nanocomposites with the purpose of plasticization, i.e. lowing the T g value, or enhancing the impact strength, or promoting the thermal properties of PVC .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of POSS nanostructured chemicals have been prepared which contain one or more different organofunctional derivatives, and have been introduced into PVC nanocomposites with the purpose of plasticization, i.e. lowing the T g value, or enhancing the impact strength, or promoting the thermal properties of PVC . Nevertheless, the plasticization and thermostability effects of POSS derivatives on PVC, especially the influence of interaction between POSS derivatives and PVC on these two effects, are not taken into account as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Known as the smallest possible silica particles, polyhedral oligomeric silsesquioxane (POSS) has been attracting a great deal of attention during the past decades. Owing to the surrounding organic groups, POSS is compatible with most polymers, such as polyethylene, epoxy, polyurethane, chlorinated polyethylene, polyamide, and polystyrene. However, the morphology of POSS in polymer matrix, which is responsible for the modification effect, intensively depends on the incorporation method of POSS.…”
Section: Introductionmentioning
confidence: 99%